Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Di Madrasah Aliyah Ikhwanul Muslimin Kabupaten Serdang Bedagai - Al-Hasyim, Ramdani; Kasran; Rambe, Masrina (STAI Tebing Tinggi Deli, 2024)
This research is included in quantitative research. Quantitative research is research that uses numbers either directly taken from research results or data processed using statistical analysis. The results of the study show that the Problem Based Learning Model at the Rohani Ikhwanul Muslimin Islamic Senior High School in Serdang Bedagai Regency is included in the moderate category, which is in the interval of 19.46-23.66 with an average value of 21.57. Student learning outcomes in the subject of aqidah akhlak at the Rohani Ikhwanul Muslimin Islamic Senior High School in Serdang Bedagai Regency are included in the moderate category, which is in the interval of 63.97 - 76.77 with an average value of 70.38. The t-count value which is greater than the t-table and the sig value which is smaller than 0.05 indicate a significant influence of the Problem Based Learning model on student learning outcomes. The Adjusted R² value of 0.347 indicates that 34.7% of the variation in student learning outcomes can be explained by the application of the Problem Based Learning model, while 65.3% is influenced by other factors.